Análisis del impacto socio-económico de las ferias de inclusión social impulsadas por el Gobierno Provincial de Pichincha en la parroquia de Machachi del cantón Mejía año 2011-2014 - Murgueytio Jarrín, Doris Karina (2015)
Inclusive Fairs are a mechanism to generate Economic Inclusion, given that they run a part of the Popular and Solidary Economy project as a different way of producing, selling and buying, thus creating/generating inclusion through the implementation/enforcing of strategies and the use of tools to achieve more equitable access to the market for smallholders. Among the new strategies of the Provincial Government of Pichincha directly aimed at raising the level of social and productive development of its inhabitants, Social Inclusion Fairs are developed in Canton Mejia. This strategy focuses on creating products whose commercialization and sale would allow the strengthening of the production in the Popular and Solidary Economy (PES) and generate public policies promoting job creation, short term redistribution of wealth, closing gaps, building equity, productive citizen participation, strengthening substantive democracy and creating life opportunities, also mitigating barriers that these kinds of projects face. It is for this reason that the objective of the Mejia Center for Economic Development is improving income, quality of life and capacity of urban and rural families, actors of the PES in the Pichincha Province. Based on the research conducted on suppliers and consumers of the Social Inclusion Fair, were revealed important and relevant socio-economic aspects generated by this fair in all the involved parties. The information that was obtained will serve as a basic tool in the decision making of the Direction of Solidary Economy of the Provincial Government of Pichincha.